Dampak Orientasi Kualitas Strategi Terhadap Kemampuan Inovasi dan Pertumbuhan Bisnis Berkelanjutan pada Perusahaan Jasa di Yogyakarta - Muhammad Hasan Ar Rizqi; Dessy Isfianadewi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to explain the impact of strategic quality orientation on innovation capabilities and sustainable business growth with the object of research is a company engaged in the service sector in the Yogyakarta area. Where there is a role for exploratory innovation and exploitative innovation as a form of innovation capabilities that has a mediating role in this research. A strategic quality orientation and the development of innovation are needed by service companies due to the ever-growing globalization, which causes service companies to continue to innovate consumer demand and compete in a tight market. The sample used in this study is 104 respondents who are owners or managers of companies spread across the Yogyakarta area. The sampling technique used was convenience sampling. The analytical technique used is SEM analysis and processed with the AMOS version 24 application. The results show that there is a positive and negative influence between the quality orientation of the strategy with exploratory and exploitative innovation, as well as sustainable business growth.